Innovation performance and technological collaboration with business partners in family firms - Gjergji, Rafaela; Lazzarotti, Valentina; Visconti, Federico; Garcia Marco, Teresa (Piccola Impresa / Small Business, 2020)
This research examines how the family status of the business and the degree of family involvement in the management of family firms moderate the relationship between business-partner collaboration and technological innovation performance. We provide empirical evidence by using a panel data of roundly 12,000 observations on Spanish manufacturing firms via regression analysis. Results show that the family status of the firm moderates the relationship between business-partner collaboration and innovation in a way that it reduces the likelihood of achieving higher innovation performance. Furthermore, within the group of family firms, the interaction between the degree of family involvement in the management and the business-partners collaboration has a negative and significant impact on the innovation performance.